Аналіз методу лінійного криптоаналізу - Федірко, Д. Д. (ХНУРЕ, 2024)
The article is devoted to the consideration of the main methods of cryptanalysis of string and block encryption systems. As an example, the article analyzes the most well-known methods of cryptanalysis - for linear codes: the method of full key search, side attacks, for block codes: full (total) key search, the method of meeting in the middle, differential cryptanalysis. Particular attention is paid to the method of linear cryptanalysis. After the analysis of open sources of information, an overview of the chosen method, its essence, advantages, disadvantages and scope of application was carried out.
Keywords: криптоаналіз; cryptanalysis